Ibn Surayj’s Ijma’a’ through his book “The Deposits for the Texts of the Shari’a” (collectively) - Anis rehoune (Journal of Science and Knowledge Horizons, 2023)
This study aims to demonstrate the interest of Muslim theologians in the history of Ijma (consensus), we presented this study by addressing the importance of this research and its characteristics, the concept of Ijma and its binding force, the biography of the diligent Imam Ibn Sarij Al-shafi’i (D. 306 h), and its status between the jurists of Islamic jurisprudence schools in general, and Shafi’i’s school in particular, the importance of his book « Al-wadaa'ee' limanṣūṣ Al-sharaa'ih», followed by the 98 related Ijma in his book after induction, and theirs classification in accordance with the categories of Islamic jurisprudence, in order to find out the positions of Ijma, that helps the students to conceive the issue and avoid objecting the one that has been already settled through Ijma. The scholars consider that knowing the positions of Ijma is one of Ijtihad’s (reasoning effort) requirements.